Quantitative analysis and human health risk assessment of heavy metals in paddy plants collected from Perak, Malaysia - Anak Sibuar, Agatha; Zulkafflee, Nur Syahirah; Selamat, Jinap; Ismail, Mohd Razi; Lee, Soo Yee; Abdull Razis, Ahmad Faizal (MDPI, 2022)
Rice is one of the major crops as well as the staple food in Malaysia. However, historical mining activity has raised a concern regarding heavy metal contamination in paddy plants, especially in Perak, a state with major tin mining during the late nineteenth century. Therefore, the objective of this study is to investigate the heavy metals (As, Cd, Pb, Cu, Cr) contamination in paddy soils and paddy plants in three districts in Perak. The content of heavy metals was determined using ICP-MS, while the absorption and transferability of heavy metals in the paddy plants were investigated through enrichment (EF) and translocation (TF) factors. Principal component analysis (PCA) was employed to recognize the pattern of heavy metal contaminations in different sampling areas. Health risk assessment was performed through calculation of various indices. The quantification results showed that root contained highest concentration of the studied heavy metals, with As exhibiting the highest concentration. The EF results revealed the accumulation of As, Cu, and Cr in the rice grains while PCA showed the different compositional pattern in the different sampling areas. The health risk assessment disclosed both noncarcinogenic and carcinogenic risks in the local adults and children. Overall, findings from this study show that heavy metal contamination poses potential health risks to the residents and control measure is required.